The dynamic interdependencies between Income inequality, public debt, and inflation rate: a PVAR model approach - Oliveira, João Pedro Gonçalves Marques de (2022)
The current dissertation presents an empirical analysis of the relationship between income inequality, inflation, and public debt in 14 developed economies. For this, a Panel VAR model is estimated for an annual balanced panel data between 1980 and 2019, where it is taken into account the endogenous relationship between the variables. This study also includes the use of a heterogeneous model, Global VAR, where individual country specifications are taken into account. In relation to the homogeneous model, it is concluded that the positive change in income inequality results in a decrease in public debt over 4 years, after the introduction of the shock. In turn, a change in public debt results in a decrease in income inequality, at the time of the shock, followed by an increase in inequality in the medium term (2nd year to 4th year). A shock to inflation reduces the accumulation of debt in the short term (1st year), showing a positive and significant trend from the 2nd year onwards. In the results of the heterogeneous model, we see that the countries with the most statistically significant results are: Portugal, Spain, France, and Italy. In these cases, the results reflect statistical significance in the responses of the Gini Index, both to an inflation shock and to an increase in public debt. To date, this work is pioneer, as the relationship between these variables has never been empirically explored, namely in a context of time-series analysis.